Op maat van het midden- en kleinbedrijf (Staatsuitgeverij, 1987)
(Rapporten aan de regering; 1987, no.30). Dl. 1. 40 p. Dl. 2. Preadviezen ; door A.F.M. Nijsen, B. Nooteboom, C.W. Kroezen [et al.], 222 p.